Welfare effects of vegetable commercializatino: Evidence from smallhoder producers in Kenya - Beatrice W. Muriithi; Julia Anna Matz (University of Bonn, Center for Development Research (ZEF), 2014)
We investigate the impact of smallholder vegetable commercialization through the export and domestic market channels on household income and assets in Kenya. We use a survey panel dataset, which allows us to control for unobserved heterogeneity across households, and show that the commercialization of vegetables through both market channels contributes positively to welfare, even when addressing the issue of selection into commercialization. While the production of vegetables for the export market is consistently associated with income in a positive way, the results for asset holdings as the measure of household welfare are weaker and supportive only for the domestic market channel, which weakens the notion of smallholder commercialization being a 'pro-poor' strategy.
Keywords: O12; O13; Q13; Q17; 330; horticulture; commercialization; welfare; poverty; smallholders; Kenya